KONSEP PENDIDIKAN TERPADU DAN STRATEGI PEMBELAJARANNYA - Muzhoffar Akhwan (Islamic University of Indonesia, 2002)
The integrated education demands the enjoyable learning and professional teachers. The article below traces an integrated education concept and its learning strategy. The existence of professional teacher means that they can develop internal individual's intellectualities, for instance the potential that still does not appear from learners. The integrated learning will make the material of lesson that taught denotes a valuable unity in the learners' live. The valuable learning experience at school constitutes becoming the demand of the future that needs a strong creativity and mental facing the challenging of future. Besides, the learners have a high education, skill and professionalism. The integrated learning is very useful for the learners especially for whom that needs particular education, because the learners pay attention to the strategy of this learning so that this strategy can motivate the learners. Therefore, it is expected that the outcome of education can solve the problems that possible emerge in their lives including creating a new field of endeavor.